Influence of Habitat Structure and Ecological Zones on Amphibian Diversity in Rivers State, Nigeria - Ekerette I B; Robert B; Nwachukwu K; Laku C B; Amuzie C C (Journal La Lifesci, 2021)
This study investigates the influence of habitat structure on the species diversity of anurans of Rivers State, Nigeria. This research was conducted between 2015 and 2019. The survey covered seven Local Government Areas (LGAs) and three ecological zones (lowland forest, freshwater swamp and short mangrove). The habitats included farmlands, fallow areas, swamps, streams and inundated areas, bush paths, human settlements and forested areas. Visual encounter and acoustic survey methods were used and species identification was aided by appropriate taxonomical keys. Diversity indices were computed using Past-exe statistical software. Nineteen amphibian species were encountered including members of the Arthroleptidae, Bufonidae, Dicroglossidae, Ranidae, Hyperoliidae, Ptychadenidae and Pipidae. Freshwater swamps and short mangrove ecological zones (characterized by human settlements and farmlands) had the lowest diversity of two and five amphibian species, respectively. The highest diversity comprised of eighteen amphibian species was recorded in forested habitats of the lowland forest/freshwater swamp ecological zone. 569 individuals were encountered at lowland forest/freshwater swamp ecological zone; 215 at lowland forest; 60 at short mangrove; and 28 at freshwater swamp ecological zone. Shannon diversity was highest in the lowland/freshwater swamp ecological zone (H=2.12) and lowest in the freshwater swamp zone (H=0.52). The results show that forested habitats comprised of the combination of lowland forest and freshwater swamp ecosystems host a greater diversity of amphibian species. We therefore recommend that lowland and freshwater swamp ecosystems in the State should be protected to support greater diversity of amphibians.